PENGETAHUAN IBU HAMIL DAN DUKUNGAN KELUARGA PADA KEJADIAN KEHAMILAN USIA MUDA REMAJA - Andriana, Kiki; Diniyati, Taty Nurti (JURNAL MEDIA KESEHATAN, 2018)
Unwanted teenage pregnancies are very embarrassing and can damage their future, therefore some teenagers have an abortion to abort their pregnancy. This research is an analytical research using Cross Sectional approach. The study population was all pregnant women from July to September as many as 370 pregnant women. The sample in this study were 82 respondents. The sampling technique was carried out by means of quata sampling. Data collection was carried out by filling out the questionnaire carried out on October 23 to November 2, 2017. Data analysis was used chi-square with p-value 0.005. The results showed that most respondents did not experience pregnancy at a young age, lacked knowledge and had negative family support. Based on the results of the analysis there is a significant relationship between knowledge and family support with the incidence of pregnancy at a young age with p-value, namely p = 0.033 and p = 0.030. Respondents' knowledge can be improved by conducting counseling, disseminating fanplet, health promotion, and activeness of respondents seeking information about pregnancy at a young age, attending formal or non-formal health education namely consulting with health workers and respondents can seek information through print and electronic media.